The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.48550/arxiv.2201.01890
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Shadows of magnetically charged rotating black holes surrounded by quintessence

Chengxiang Sun,
Yunqi Liu,
Wei-Liang Qian
et al.

Abstract: In this work, we study the optical properties of a class of magnetically charged rotating black hole spacetimes. The black holes in question are assumed to be immersed in the quintessence field, and subsequently, the resulting black hole shadows are expected to be modified by the presence of the dark energy. We investigate the photon region and the black hole shadow, and in particular, their dependence on the relevant physical conditions such as the state parameter of the quintessence, the angular momentum, an… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…In the study of the perturbations of the state parameter, Chakrabarty et al found that the perturbations with high value the parameter are unstable [52]. In axisymmetric black holes, the quintessence-like matter changes the shape of the black hole shadow [53]. To verify the validity of calculating QNMs by shadow radii, we get QNMs by the sixth order WKB approximation method and shadow radius of the black hole, respectively.…”
Section: Introductionmentioning
confidence: 98%
“…In the study of the perturbations of the state parameter, Chakrabarty et al found that the perturbations with high value the parameter are unstable [52]. In axisymmetric black holes, the quintessence-like matter changes the shape of the black hole shadow [53]. To verify the validity of calculating QNMs by shadow radii, we get QNMs by the sixth order WKB approximation method and shadow radius of the black hole, respectively.…”
Section: Introductionmentioning
confidence: 98%